Angsana (Pterocarpus indicus) sebagai Bioindikator untuk Polusi di Sekitar Terminal Lebak Bulus - Waryanti, Waryanti; Sugoro, Irawan; Dasumiati, Dasumiati (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2015)
Jakarta as one of the biggest city in Indonesia, it own more than 6.506.244 units of motor vehicles. The combustion of fossil fuels in motor vehicles can cause air pollution. Station is represented as one of heavy pollution location. The observation has be done by abservate the amount of vehicles, stomatal characteristic, and weight of dust on Angsana leaves, which growth around Lebak Bulus station. As the result, there is relation between weight of dust on leaf and stomatal characteristic, with r value = 1. The level weighat of dust on leaf has effect to stomata conditions, such as surface of stomata become smaller and shape of stomata become irregular, but amount and size of stomata didn’t influenced. In some case, leaf can be identifid by visible symptoms of injury such as chlorotic at the leaf veins, which caused by SO2 or black or brown flecks at the leaf veins, which caused by NOx.